Detecting Suicidal Content on Social Media Using Machine Learning (International Journal of Food and Nutritional Sciences, 2023)
-Individuals who suffer from suicidal ideation frequently express their views and ideas on socialmedia. Thus, several studies found that people who are contemplating suicide can be identified by analyzingsocial media posts.